1976
DOI: 10.1128/jvi.19.3.775-781.1976
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sindbis virus temperature-sensitive mutants in cultured BHK-21 and Aedes albopictus (Mosquito) cells

Abstract: A number of the temperature-sensitive mutants of Sindbis virus originally isolated and characterized by Burge and Pfefferkorn (1966, 1968) were reexamined for their abilities to grow and complement one another in cultured BHK-21 and Aedes albopictus (mosquito) cells. The response of the mutants to conditions of high and low temperature was similar in cultured cells of both the vertebrate and invertebrate hosts. Complementation experiments in BHK-21 cells produced growth patterns similar to those described by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 13 publications
1
67
0
Order By: Relevance
“…3). The higher multiplicity of infection was used to be certain that all of the cells were infected, even though in a previous study we demonstrated that all of the cells in a mosquito culture could be infected by 50to 100-PFU multiplicities under the conditions used for infection in this study (12).…”
Section: Growth Of Sindbis Virus In Cultured Mosquito Cells the Growmentioning
confidence: 80%
See 4 more Smart Citations
“…3). The higher multiplicity of infection was used to be certain that all of the cells were infected, even though in a previous study we demonstrated that all of the cells in a mosquito culture could be infected by 50to 100-PFU multiplicities under the conditions used for infection in this study (12).…”
Section: Growth Of Sindbis Virus In Cultured Mosquito Cells the Growmentioning
confidence: 80%
“…Research Unit, New Haven, Conn.) and were cultured in the medium of Mitsuhashi and Maramorosch (9) as described previously (12). BHK-21 cells were provided by Peter Faulkner (Queens University, Ontario, Canada) and were grown in Eagle medium (4) supplemented with 10% calf serum.…”
Section: Materials and Methods Cells Virus And Media Aedes Albopicmentioning
confidence: 99%
See 3 more Smart Citations